Giant Coronary Aneurysms in a Young Adult Patient with Kawasaki Disease - Canino-Rodríguez, Alexis; Cox, Rafael A. (Puerto Rico Health Sciences Journal, 2008)
Kawasaki disease is an acute, self-limited vasculitis of childhood and the principal cause of acquired heart disease in children in several parts of the world. Its major morbidity and mortality is related to the development of coronary aneurysms. The long-term impact of this disease in adults is not known, however, clinically silent coronary artery aneurysms may be recognized after a sudden cardiac event, even death. We report a case of Kawasaki disease in a young asymptomatic Puerto Rican man who presented to our Adult Cardiology Clinic with multiple giant coronary aneurysms. A brief review of the epidemiology, etiology, pathophysiology, clinical features, therapeutic modalities, prognosis and complications of this condition is also included.